Simulation study of the vibration of a gunungan. (29th October 2019) - Adi, Gandha Satria; Parikesit, Gea Oswah Fatah; Kusumaningtyas, Indraswari
One of the characters in Wayang Kulit art that has an important role almost in all performances is the gunungan . It has a nearly triangular shape with a pair of gapit that clamps on the middle. During the performance, the gunungan is always vibrated by the master puppeteer to create a more lively shadow. This vibration can be analysed deeper if we study the characteristics of a gunungan model, namely its natural frequencies and mode shapes. The gunungan simulation in this study is the first simulation in the world that tried to make as real as possible the gunungan shape based on actual condition. The gunungan model is built using Abaqus/CAE 6.11-1. In order to make the model properly, we used a validated model (i.e., a cantilever and a rectangular model) as a reference. The results showed that the holes (or the percentage of close area) and the rings have direct impact to the natural frequencies and mode shapes of the model.